Quality Health Improvement Using GEN SMART Mendala in Mendala Village - Richa Amalia; Hangge Daud Wahyudi; Sunarto; Erwin Hendra Putra (Prospect Publishing, 2023)
Indonesia, a country with a population of 281 million, poses a big challenge in managing public health. Currently Indonesia is facing a triple burden of various disease problems, Indonesia is also experiencing another health burden, namely stunting. Stunting is not only a matter of height but the most dangerous thing is the child's low ability to learn, mental retardation, and the third is the emergence of chronic diseases. The President of Indonesia in the BKKBN National Working Meeting stated that,